Morphological, Structural, and Optical Properties of Doped/Codoped ZnO Nanocrystals Film Prepared by Spin Coating Technique and Their Gas Sensing Application. (16th May 2022) - Verma, Neha; Jagota, Vishal; Alimuddin,; Alguno, Arnold C.; Rakhra, Manik; K., Chanthirasekaran; Dugbakie, Betty Nokobi
Abstract : In today's world of electronics, nanomaterial applications pose a challenge. The spin coating approach was used to create nanostructured ZnO with wurtzite structure in a recent study. Antimony doping, aluminum, and antimony codoping with 2.0 percent were used to make these films. The impact of doped and codoped films on structural, optical properties, and morphological has been examined using a variety of characterization approaches. A ZnO nanocrystal with a diameter of 20-30 nm was discovered using XRD (X-ray diffraction). According to SEM (scanning electron microscope) scans, the grain size is in the 80-120 nm region. The use of Fourier transform infrared spectroscopy (FTIR) to detect elemental elements was studied, and the peak at 400-520 cm -1 was identified as ZnO. The optical properties of doped and codoped ZnO were checked, and it was discovered that antimony-doped ZnO has a larger band gap than Al and antimony-codoped ZnO. This proved that ZnO may be used in gas sensors and solar cells. The gas response of a static gas sensor system based on Sb-doped films was measured and compared to Al- and Sb-codoped films in the presence of ethanol vapor.